Bone defect repair on the alveolar wall of the maxillary sinus using collagen membranes and temporal fascia: an experimental study in monkeys - Silva, Adalberto Novaes; Oliveira, José Américo de [UNESP]; Jamur, Maria Célia; Junqueira, José Ari Gualberto; Correa, Vani Maria; Lima, Wilma Terezinha Anselmo (FapUNIFESP (SciELO), 2011)
Few studies has been done using guided bone regeneration in maxillary sinus defects. AIM: To assess the bone repair process in surgical defects on the alveolar wall of the monkey maxillary sinus, which communicates with the sinus cavity, by using collagen membranes: Gen-derm - Genius Baumer, Pro-tape - Proline and autologous temporal fascia. MATERIALS AND METHODS: In this prospective and experimental study, orosinusal communications were performed in four tufted capuchin monkeys (Cebus apella) and histologic analysis was carried out 180 days after. RESULTS: In the defects without a cover (control), bone proliferation predominated in two animals and fibrous connective tissue predominated in the other two. In defects repaired with a temporal fascia flap, fibrous connective tissue predominated in three animals and bone proliferation predominated in one. In the defects repaired with Gen-derm or Pro-tape collagen membranes there was complete bone proliferation in three animals and fibrous connective tissue in one. CONCLUSIONS: Surgical defect can be repaired with both bone tissue and fibrous connective tissue in all study groups; collagen membranes was more beneficial in the bone repair process than temporal fascia or absence of a barrier.

Poucos experimentos têm sido conduzidos utilizando o princípio da regeneração óssea guiada nas perfurações ósseas do seio maxilar. Objetivo: Avaliar o processo de reparo ósseo em defeitos cirúrgicos experimentais realizados na parede alveolar do seio maxilar, comunicando-se com a cavidade sinusal utilizando membranas de colágeno e fáscia temporal. Materiais e Métodos: Neste estudo prospectivo, experimental, foram realizados defeitos ósseos em paredes alveolares dos seios maxilares comunicando-se com as cavidades sinusais de quatro macacos pregos (Cebus apella) com membranas de colágeno Gen-derm - Genius Baumer, Pro-tape - Proline e fáscia temporal autóloga e análises histológicas após 180 dias. Resultados: No defeito experimental sem cobertura com métodos de barreira predominou proliferação óssea em dois animais e nos outros dois, tecido conjuntivo fibroso; no grupo em que foi utilizado fáscia temporal predominou tecido conjuntivo fibroso em três animais e proliferação óssea em um animal; nos grupos com membranas de colágeno Gen-derm Protape houve completa proliferação óssea em três animais e predomínio de tecido conjuntivo fibroso em um animal. Conclusões: Os defeitos cirúrgicos experimentais podem ser reparados, tanto por tecido ósseo como por tecido conjuntivo fibroso, e o uso de membranas de colágeno trouxeram benefícios ao processo de reparo ósseo
Reparo em defeito ósseo da parede alveolar do seio maxilar utilizando membranas de colágeno e fáscia temporal: estudo experimental em macacos
Keywords: Bone regeneration; Collagen; Fascia; Maxillary sinus; Membranes; Colágeno; Fáscia; Membranas; Regeneração óssea; Seio maxilar